You Owe Me - Ulrike Malmendier; Klaus Schmidt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
In business and politics, gifts are often aimed at influencing the recipient at the expense of third parties. In an experimental study, which removes informational and incentive confounds, subjects strongly respond to small gifts even though they understand the gift giver's intention. Our findings question existing models of social preferences. They point to anthropological and sociological theories about gifts creating an obligation to reciprocate. We capture these effects in a simple extension of existing models. We show that common policy responses (disclosure, size limits) may be ineffective, consistent with our model. Financial incentives are effective but can backfire.
Keywords: C91; D62; D73; I11; 330; Gift exchange; externalities; lobbyism; corruption; reciprocity; social preferences